PENINGKATAN KEMAMPUAN REPRESENTASI MATEMATIS DAN MINAT BELAJAR MATEMATIKA PADA SISWA SEKOLAH MENENGAH PERTAMA DENGAN PENDEKATAN CONCRETE-PICTORIAL-ABSTRACT (CPA) BERKELOMPOK - Azmidar, _ (2017)
The main purposes of this research were to analyze the enhancement of students' representation ability and the attainment of students' mathematical learning interest who received the grouping of the Concrete-Pictorial-Abstract (CPA) approach. This research was a quasi-experimental with a group control non-equivalent design. Population of this research was students grade VII in one of school in Enrekang. This research uses two classes which selected by purposely, that are an experimental group who obtain the grouping of the Concrete-Pictorial-Abstract approach and a control group who received conventional learning. The instrument which used in this research were mathematics prior knowledge, representation ability test, and mathematical learning interest scale. Based on statistical analysis, indicated that: (1) Enhancement of the students' mathematical representation ability who received the grouping of the Concrete-Pictorial-Abstract (CPA) approach higher than the students who get the conventional learning (2) In the high and middle categories' of mathematical prior knowledge, the enhancement of students' mathematical representation ability who received the grouping of the Concrete-Pictorial-Abstract (CPA) approach higher than students who get the conventional (3) Students' mathematical learning interest who received the grouping of the Concrete-Pictorial-Abstract (CPA) approach higher than students who get the conventional learning (4) In the low, middle, and high categories of mathematics prior knowledge, students' mathematical learning interest who received the grouping of the Concrete-Pictorial-Abstract (CPA) approach higher than students who get the conventional learning. -------- Penelitian ini bertujuan untuk menganalisis peningkatan kemampuan representasi matematis siswa dan pencapaian minat belajar matematika siswa yang memperoleh pembelajaran dengan pendekatan Concrete-Pictorial-Abstract (CPA) Berkelompok. Penelitian ini merupakan penelitian kuasi eksperimen dengan desain kelompok kontrol non-ekuivalen. Populasi dalam penelitian ini adalah siswa kelas VII pada satu Sekolah di Enrekang. Penelitian ini menggunakan dua kelas yang dipilih secara purposif yaitu kelas eksperimen yang memperoleh pembelajaran dengan pendekatan Concrete-Pictorial-Abstract (CPA) berkelompok dan kelas kontrol yang memperoleh pembelajaran biasa. Instrumen yang digunakan dalam penelitian ini berupa data kemampuan awal matematis (KAM), tes kemampuan representasi matematis, dan skala minat belajar. Berdasarkan hasil analisis data disimpulkan bahwa: (1) Peningkatan kemampuan representasi matematis siswa yang memperoleh pembelajaran dengan pendekatan Concrete-Pictorial-Abstract (CPA) Berkelompok lebih tinggi daripada siswa yang memperoleh pembelajaran biasa (2) Pada kategori KAM tinggi dan KAM sedang, peningkatan kemampuan representasi matematis siswa yang memperoleh pembelajaran dengan pendekatan Concrete-Pictorial-Abstract (CPA) berkelompok lebih tinggi daripada siswa yang memperoleh pembelajaran biasa (3) Minat belajar matematika siswa yang memperoleh pembelajaran matematika dengan pendekatan Concrete-Pictorial-Abstract (CPA) Berkelompok lebih lebih tinggi daripada siswa yang memperoleh pembelajaran biasa (4) Pada kategori KAM tinggi, sedang dan KAM rendah, minat belajar siswa yang memperoleh pembelajaran dengan Concrete-Pictorial-Abstract (CPA) berkelompok lebih tinggi daripada siswa yang memperoleh pembelajaran biasa.